Penerapan Model Pembelajaran Improve pada Materi Nahwu dalam Meningkatkan Maharoh Qiro’ah Santri di Pondok Pesantren - Mualim Wijaya; Faridy Faridy; Nurul Makkiyah (Communautaire: Journal of Community Service, 2023)
This study focuses on the implementation of the "Improve" learning model for Nahwu material at PP Darul Lughah Wal Karomah, Sidomukti Kraksaan Probolinggo. The research objective is to evaluate the impact of this learning model on the improvement of maharoh qiro'ah. A qualitative method with a case study approach was used, involving 20 students as respondents, and data collection techniques included observation, interviews, and documentation. The results of data analysis using descriptive analysis showed that the implementation of the "Improve" model has resulted in a positive impact. Significant changes were seen in the students' learning enthusiasm in class and their ability to apply the rules of Nahwu when reading the Yellow Book. The implications of this model have successfully overcome boredom and monotony in Nahwu learning, providing an effective alternative to enhancing students' understanding and motivation to learn in the pesantren environment.